Keeping Teacher Professional Development Performance in Teaching: The Role of Interest Development in the Era of Technological Advance - Nanik Hindaryatiningsih; Muhamad Sholeh; Jafar Ahiri; Fina Amalia Masri; Ansor Putra; Omasrianto Omasrianto; Yuniarti Ahiri; Jamal Harimudin (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study examines teachers' professional performance in more depth through interest development in the era of technological advancement. Method: The research approach uses a mixed-method research design with an explanatory research method. The population of this study were teachers of Teacher Professional Education (TPE) at Halu Oleo University. The number of respondents in this study was 340 people. The data collection process used questionnaires, discussion forums, and documents. Results: The results of the study indicate that 1) the clarity and structure aspects require improvement in the ability to develop teaching that combines material content with relevant character values ​​in the digital era, 2) the practical relevance aspect requires the development of teaching skills that combine student learning experiences with learning objectives, 3) the cognitive activation aspect has been carried out by teachers well through periodic teaching evaluations, and 4) the collaboration interest aspect needs to be improved so that the problems faced by each teacher have more varied input for resolution. From the findings, it can be concluded that the cognitive activation aspect of interest development has affected the quality of teacher teaching. However, interest development is essential in achieving educational quality because, in professional development, teachers make various efforts to improve their skills or competencies to carry out teaching tasks. Novelty: The findings show novelty that contributes to the understanding of knowledge about the interesting aspect of teacher development as the most important part of improving the quality of teaching. Two important points of novelty are self-reflection and self-competence. Improvement must be carried out by developing science and technology so that the teaching can utilize digital technology as a learning resource.